1978
DOI: 10.1111/j.1651-2227.1978.tb16347.x
|View full text |Cite
|
Sign up to set email alerts
|

HAEMATOPOIETIC STEM CELLS (CFUc) IN HUMAN CORD BLOOD

Abstract: Colony forming units (CFUc) giving rise to myelocytic colonies in methylcellulose cultures were found among non-adherent mononuclear cells of human cord blood with a frequency of one in 1678. The number decreased makredly during the first 8 to 10 days of life. They were rarely detected in adult blood by this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 16 publications
1
25
0
3
Order By: Relevance
“…5g). DISCUSSION The presence of a large number of CFU-C in the cord blood has been shown in culture using agar or methyl cellulose (2,3,(11)(12)(13)17) . Observations with light and electron microscope have revealed that the cord blood contains premature myeloid and monocyte cells (15,22).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5g). DISCUSSION The presence of a large number of CFU-C in the cord blood has been shown in culture using agar or methyl cellulose (2,3,(11)(12)(13)17) . Observations with light and electron microscope have revealed that the cord blood contains premature myeloid and monocyte cells (15,22).…”
Section: Resultsmentioning
confidence: 97%
“…Several papers have recently confirmed that newborn peripheral blood and umbilical cord blood also contain a large number of CFU-C when assayed in agar or methyl cellulose (2,3,(11)(12)(13)17). It is also known that the cord blood cells have the ability to form granulocytic colonies even without conditioned medium in methyl cellulose (17). The existence of CFU-G; E in the cord blood has also been reported (3).…”
mentioning
confidence: 99%
“…It is interesting to point here the fact that even if embryonic stem cells have been suggested to exist in 1908 by Maximov [208] (who was the first one to call them this way), evidence of existence of stem cells in the bone marrow was only proven in 1963 by McCulloch and Till [50]. Fifteen years later, in 1978, HSC were found in the blood of the umbilical cord [229]. And we had to wait until 1997 to get a link between leukemia and hematopoietic stem cells showing the first cases of cancer stem cells [66].…”
Section: Hematopoiesis: Brief Biological Backgroundmentioning
confidence: 98%
“…It was only in 1978 that stem cells were discovered in human cord blood, 1 followed by the development of first in vitro stem cell line in mice (1981), 2,3 generation of embryonic stem cell lines from hamster (1988) 4 and later from primate (1995). 5 A huge progress was achieved in 1998 when cells from the inner cell mass of early embryo were isolated and first embryonic stem cells were developed.…”
Section: Editorialmentioning
confidence: 99%